Design and performance of the Hotrod melt-tip ice-drilling system - W. Colgan; C. Shields; P. Talalay; X. Fan; A. P. Lines; J. Elliott; H. Rajaram; K. Mankoff; M. Jensen; M. Backes; Y. Liu; X. Wei; et al. (Geoscientific Instrumentation, Methods and Data Systems, 2023)
We introduce the design and performance of an electrothermal ice-drilling system designed to insert a temperature sensor cable into ice. The melt tip is relatively simple and low-cost, designed for a one-way trip to the ice–bed interface. The drilling system consists of a melt tip, umbilical cable, winch, interface, power supply, and support items. The melt tip and the winch are the most novel elements of the drilling system, and we make the hardware and electrical designs of these components available open-access. Tests conducted in a laboratory indicate that the melt tip has an electrical energy to forward melting heat transfer efficiency of ∼35 % with a theoretical maximum penetration rate of ∼12 m h −1 at maximum 6.0 kW power. In contrast, ice-sheet testing suggests the melt tip has an analogous heat transfer efficiency of ∼15 % with a theoretical maximum penetration rate of ∼6 m h −1 . We expect the efficiency gap between laboratory and field performance to decrease with increasing operator experience. Umbilical freeze-in due to borehole refreezing is the primary depth-limiting factor of the drilling system. Enthalpy-based borehole refreezing assessments predict refreezing below critical umbilical diameter in ∼4 h at − 20 ∘ C ice temperatures and ∼20 h at − 2 ∘ C . This corresponds to a theoretical depth limit of up to ∼200 m, depending on firn thickness, ice temperature, and operator experience.